MEPES: Methodology for evaluating the performance of e-mail servers - Torres Calderón, Pedro Alexis (2018)
The purpose of the article was to develop a methodology for evaluating performance of e-mail servers and to compare the performance of e-mail servers based on free software (freeware and open source software) with the performance of payment licensed e-mail servers, with an integrated focus. For obtaining this purpose, a descriptive and experimental study was developed, which population included 33 e-mail servers. Two e-mail servers with free license (Sendmail and Postfix) and two e-mail servers with payment license (Microsoft Exchange and Lotus Domino) were compared. For evaluating the performance (antispam capacity, antivirus filtering, and server resource consumption), special applications for that purpose were used. Finally, it was determined that the two products of e-mail servers implemented with free software (Sendmail and Postfix) had higher performance than the two licensed e-mail servers (Microsoft Exchange and Lotus Domino) which were implemented, under the conditions given in this research.